The question is....rewrite this summation so the index variable is k and the starting value is 5

so. j = 1, k = 5....so j = k -4

So plugging these in I come up with:

Is this correct?

Printable View

- April 11th 2009, 09:35 PMrelytrewrite summation

The question is....rewrite this summation so the index variable is k and the starting value is 5

so. j = 1, k = 5....so j = k -4

So plugging these in I come up with:

Is this correct? - April 11th 2009, 10:03 PMspearfish
if j = k - 4, then j + 1 = (k -4) + 1 = k-3, not k+5

- April 11th 2009, 10:11 PMrelyt
Doh....I had it written down incorrectly. thanks